Extraction the First Permanent Molar With Poor Prognosis in Mixed Dentition Period - B Seraj (Tehran University of Medical Sciences, 2002)
Whenever the first permanent molar is extracted or its long- term prognosis is poor, before taking any steps, a full clinical and radiographic evaluation associated with patients dental models investigation is necessary to determine the following cases:The quality and quantity of dentition, teeth missing, occlusion, buds position, orthodontic problems, the level of parents and patient cooperation for future long term orthodontic treatment and finally patient's oral hygiene. On the basis of this information, a decision is taken about the first permanent molar extraction with poor prognosis, either of balancing or compensatory type, especially when future orthodontic treatment is improbable. The aim of this article is to explain the principles of time and sequence of first permanent molar extraction.